Análise de uma proposta de ensino de geometria descritiva baseada na perspectiva histórico-cultural - Boanova, Cecília Oliveira (2011)
This dissertation was aimed at planning, implementing and evaluating a teaching practice based on the historical-cultural perspective of Vygotsky and focused on the construction of specific knowledge about Lines (Retas), content topic of the discipline Descriptive Geometry (DG), part of the vocational course in Furniture Design at the Instituto Federal Sul-rio-grandense (Pelotas Campus). The teaching practice was developed from two pilot studies and aimed to overcome the usual difficulties of learning in this discipline, besides developing spatial reasoning in students. This kind of reasoning is seen as an important superior psychological function and the teaching practice sprang from the hypothesis that such a function can be developed through learning GD. The teaching practice was characterized by: a) offering students courses of reasoning to be imitated (in the Vygotskian sense of the term); b) going from the simplest to the most complex contents; c) using concrete materials and examples from everyday life to impart sense to the concepts; and d) using writing to systematize and deepen student learning and allow the teacher to monitor such learning. The assessment of the teaching practice was carried out by means of a quasi-experimental, qualitative design. The instruments for data collection were: focus groups; documentary analysis of exercises, tests and questionnaires, produced by the students; and unstructured observations conducted by the teacher. The content analysis of collected data indicated that there was adequate internalization of knowledge, on the part of students, albeit with varying degrees of thoroughness and time required for learning: they all passed. The analysis also suggested that these results were achieved through the dialogic and collaborative interactions that occurred between teacher and students during the exercises, assessment tests, and explanations aided by the use of concrete materials and examples of daily life. The use of writing also constituted an important tool, indicating that it can assist in the development of spatial reasoning through the conscience fostered by scientific concepts, as well as help the teacher to monitor the process of internalization of these concepts by students. The teaching practice analyzed presents potential to contribute to the discussions aimed at improving the processes of teaching and learning GD, although such practice is far from constituting a closed proposal, since some of its aspects need to be further studied and modified